Conceptualizing corporate accountability in international law: models for a business and human rights treaty - Bernaz, Nadia (Human rights review, 2021)
This article conceptualizes corporate accountability under international law and introduces an analytical framework translating corporate accountability into seven core elements. Using this analytical framework, it then systematically assesses four models that could be used in a future business and human rights (BHR) treaty: the United Nations Guiding Principles on Business and Human Rights model, the Universal Declaration of Human Rights model, the progressive model, and the transformative model. It aims to contribute to the BHR treaty negotiation process by clarifying different options and possible trade-offs between them, while taking into account political realities. Ultimately, the article argues in favour of the BHR treaty embracing a progressive model of corporate accountability, which combines ambitious development of international law with realistic prospects of state support.